Apakah Tax Planning Dapat Meminimkan atau Menambahkan Beban Pajak PPN di Perusahaan? - Shifa Miarti Aziza; Memen Kustiawan; Ida Farida Adi Prawira (Jurnal Pendidikan Akuntansi (JPAK), 2023)
VAT is considered one of the main taxes that companies need to incur and has a direct impact on a company’s costs and profits. There are several effective and ineffective ways that companies can do in optimizing the tax burden that needs to cover the company. The purpose of this study is to see how the impact of tax planning can reduce or even increase the VAT company’s tax burden. The method in this research is a Systematic Literature Review (SLR), in which the author observes articles published in the last 10 years. The results of this study reveal that tax planning on VAT can provide effective or ineffective results for companies where it is necessary to have an understanding of the company related to tax regulations in order to minimize the company’s tax burden.